'TO HAVE DARING IS LIKE A BARRIER': CICERO AND SALLUST ON CATILINE'S AUDACIA. (10th September 2015) - Unknown
Abstract : Known to us only through the spectrum of hostile sources, Lucius Sergius Catilina (108–62bc ) is an enigma. Nevertheless, one aspect of his personality seems clear. However much they differ in their evaluation of the patrician's failed coup d'état in 63bc, our main authorities, Cicero and Sallust, both assert his tremendous daring. This article will demonstrate that their agreement on this issue is deceptive. Reviewing their use of the word audacia ('daring') as an attribution typical for rebel behaviour, I will explore how its use in combination with words for madness and despair provides it with different positive as well as negative connotations. Although, as we shall see in more detail below, many scholars have either ignored the term or discussed audacia as a standard, mono-dimensional piece of invective, it is a dynamic and multifaceted word representative of the chaos of the Late Republic.